AMBIENT
  • Câu hỏi:

    Để biểu thức  \(A=\left ( 1-\frac{4}{\sqrt{x}+1}+\frac{1}{x-1} \right ):\frac{x-2\sqrt{x}}{x-1}\) , với \(x>0;x\neq 1,x\neq 4\) đạt giá trị \(A=\frac{1}{2}\) thì x phải có giá trị là:

     

    • A. 8
    • B. 16
    • C. 32
    • D. 64

    Lời giải tham khảo:

    Đáp án đúng: B

    Ta có: \(A=\left ( 1-\frac{4}{\sqrt{x}+1}+\frac{1}{x-1} \right ):\frac{x-2\sqrt{x}}{x-1}\)

    \(=\frac{x-1-4(\sqrt{x}-1)+1}{x-1}.\frac{x-1}{\sqrt{x}(\sqrt{x}-2)}\)

    \(=\frac{(\sqrt{x}-2)^2}{\sqrt{x}(\sqrt{x}-2)}=\frac{\sqrt{x}-2}{\sqrt{x}}\)

    Mà \(A=\frac{1}{2}\Leftrightarrow \frac{1}{2}=\frac{\sqrt{x}-2}{\sqrt{x}}\Rightarrow x=16\)

    ADSENSE

 

 

CÂU HỎI KHÁC

AMBIENT
?>